LENGTH-WEIGHT RELATIONSHIP, SIZE DISTRIBUTION AND ANNUAL CPUE’s OF ALBACORE IN EASTERN INDIAN OCEAN - Bram Setyadji; Budi Nugraha; Duto Nugroho (Indonesian Fisheries Research Journal, 2014)
Albacore (Thunnus alalunga, Bonnaterre, 1788) is one of the tropical tuna species in the Eastern Indian Ocean incidentally caught by the Indonesian tuna longliner. Scientific observer series data during the period of 2005 – 2012 showed that the catches were geographically distributed within the area bordered by 5 – 350 S and 75 – 1300 E. High CPUE mainly occurred in sub area between 250 and 350 S. Some biological observations indicated that immature albacore specimens were mainly recorded in areas of south of 250 S while mature albacore were concentrated in the area between 100 S and 250 S. Length – weight measurements for pooled male and female was W= 0.00008FL2.7271. The hook-rates from onboard observation showed that increasing rates occurred during 2009 to 2012. The annual landing showed that that highest occurred in 2008 and the lowest in 2011 with overall tend to decrease until 2011 and increased slightly in 2012. Series number of length frequency measurements (2005 - 2012) showed that the albacore were caught within the range of 40 – 135 cm FL and there was a tendency that the average size decreased gradually from 103 cmFL (2005) to 84 cmFL (2012). As a preliminary finding these estimates contribute as important element for consideration in the national and regional tuna fisheries management in the area.